DESCRIPTION OF TOOTH-BRUSHING BEHAVIOR BEFORE AND AFTER COUNSELING WITH ROLLING TECHNIQUE IN SDN MELONG ASIH CIMAHI - Sarwendah, Sri; Reza, Eq; Renita, Intan; Wira, Nabila (Journal of Health and Dental Sciences, 2024)
Correct and routine brushing behavior is very influential on oral cavity health. The knowledge possessed by the individual will determine his health behavior so that someone with good knowledge will know the right attitude and behavior when exposed to disease. Brushing your teeth properly and regularly is very influential on the health of the oral cavity, so there needs to be counseling on how to brush your teeth properly and correctly. This study aimed to determine the picture of brushing behavior before and after counseling with Rolling Technique in Grade 3 Students of SDN Melong Asih 5. This study used an analytical descriptive study design by conducting counseling followed by dental and oral hygiene examination with the Oral Hygiene Index Simplified (OHI-S)  index method. Based on the results obtained, it can be concluded that the OHI-S index in grade 3 students of SD Melong Asih 5 has decreased after counseling with poster media and dental pantum props that showed promising results; the rolling technique is quite effective in reducing the OHI-S index in SD Melong Asih 5 Cimahi students. DOI : 10.54052/jhds.v3n3.p281-290